2010
DOI: 10.1637/8736-032509-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza Virus H9N2 Survival at Different Temperatures and pHs

Abstract: The H9N2 avian influenza virus (AIV) subtype has become endemic in Israel since its introduction in 2000. The disease has been economically damaging to the commercial poultry industry, in part because of the synergistic pathology of coinfection with other viral and/or bacterial pathogens. Avian influenza virus viability in the environment depends on the cumulative effects of chemical and physical factors, such as humidity, temperature, pH, salinity, and organic compounds, as well as differences in the virus it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Our results showed that the 2009 pandemic A(H1N1) virus had the ability to persist in water and on glass surface for several weeks, even at 35°C. As described previously, low temperature increased virus survival [5][7], [17]. At low salinity levels (0 and 5 ppt), maximum estimated survival times varied between 698 and 1097 days.…”
Section: Discussionsupporting
confidence: 77%
“…Our results showed that the 2009 pandemic A(H1N1) virus had the ability to persist in water and on glass surface for several weeks, even at 35°C. As described previously, low temperature increased virus survival [5][7], [17]. At low salinity levels (0 and 5 ppt), maximum estimated survival times varied between 698 and 1097 days.…”
Section: Discussionsupporting
confidence: 77%
“…The reason for lack of detection in the environmental specimens is not clear, but we suspect that the high environmental temperatures in Kenya may limit the survival of any virus shed in feces by the birds. Reduced viability of several AIV subtypes has been shown to be associated with increases in temperature 24–26 . The presence of rt RT‐PCR inhibitors could also have limited influenza A viral RNA detection in these samples 22 …”
Section: Discussionmentioning
confidence: 99%
“…In most cases, viruses tend to survive better at lower temperatures (25,35,42,43), and the temperature fluctuations could result in virus inactivation. In addition, alfalfa sprouts provided a neutral pH (44), and pH ranging from 6 to 8 has been shown to be preferable for virus survival, with decreased rates of inactivation (25,42,43,45). HBSS contains salts and provides a stable pH at ϳ7.25, which is within that range.…”
Section: Discussionmentioning
confidence: 99%